The relationship between individualism-collectivism orientation and ownership of work knowledge through the mediating role of organizational citizenship behavior (an analytical study). - عامر علي حسين (Iraqi Journal for Administrative Sciences, 2024)
The current study tests the factors that determine a worker’s willingness to share acquired specific knowledge about work; These factors are represented by individualism/collectivism orientation as an independent variable and organizational citizenship behavior as a mediating variable. The teaching staff at the Technical Institute - Samawa was selected as a sample for the current study. The questionnaire form was used as the main tool for collecting data. (40) questionnaires were distributed On the study sample, the number of questionnaires that were analyzed was (36). The current study explores individualism/positivism orientation and organizational citizenship behavior and its relationship to work knowledge ownership; The results indicate that the orientation toward collectivism and organizational citizenship behavior have a negative impact on the possession of knowledge, while the orientation toward individualism and organizational citizenship behavior have a positive impact on the possession of knowledge.